2018
DOI: 10.1002/hep4.1203
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear receptors and liver disease: Summary of the 2017 basic research symposium

Abstract: The nuclear receptor superfamily contains important transcriptional regulators that play pleiotropic roles in cell differentiation, development, proliferation, and metabolic processes to govern liver physiology and pathology. Many nuclear receptors are ligand‐activated transcription factors that regulate the expression of their target genes by modulating transcriptional activities and epigenetic changes. Additionally, the protein complex associated with nuclear receptors consists of a multitude of coregulators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 107 publications
(228 reference statements)
0
8
0
Order By: Relevance
“…However, NR-based therapies usually showed poor efficacy in human beings. Today, new combined drugs targeting NRs, including dual-/triple-agonists and NR modulators, are emerging as promising pharmacologic interventions in NASH patients, with minimal negative metabolic effects 107 ( Figure 1 , Table 1 ).
Figure 1 Role of selective agonists of PPARs in NASH.
…”
Section: Ppars and Nash Treatmentsmentioning
confidence: 99%
“…However, NR-based therapies usually showed poor efficacy in human beings. Today, new combined drugs targeting NRs, including dual-/triple-agonists and NR modulators, are emerging as promising pharmacologic interventions in NASH patients, with minimal negative metabolic effects 107 ( Figure 1 , Table 1 ).
Figure 1 Role of selective agonists of PPARs in NASH.
…”
Section: Ppars and Nash Treatmentsmentioning
confidence: 99%
“…QIANQIAN LI 1,2* , NINGBO LI 1,3* , YETING ZENG 4 , XINRUI WANG 5 , JIE LI 1 , HONGYING SU 1 , MEIQIN GAO 1 and XIONGFEI HUANG 1,6 Materials and methods Cell culture. SK-Hep-1 cells were obtained from the cell bank of the Chinese Academy of Sciences.…”
Section: Nuclear Receptor Fxr Impairs Sk-hep-1 Cell Migration and Invmentioning
confidence: 99%
“…FXR was initially regarded as a multifunctional metabolic regulator involved in maintaining the hepatic homeostasis of bile acid, glucose and lipids (3,4). It has been well documented that FXR also suppresses liver carcinogenesis and progression (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of NRs are activated in a ligand-dependent manner by steroid hormones, retinoids, thyroids and products of intermediate metabolism such as bile acids, fatty acids and cholesterol derivatives (91). Still, some members of this family do not need ligand binding to regulate transcription and are classified as "orphans" (92).…”
Section: The Impact Of Nuclear Receptors On Hdl Metabolismmentioning
confidence: 99%
“…Nuclear receptors bind to specific DNA sequences called Hormone Response Elements (HREs) on the promoters of target genes either as homodimers or as heterodimers with the Retinoid X Receptor (RXR) (87). HREs Accumulating evidence reveals that the promoters of genes associated with HDL metabolism, such as apoA-I, apoA-II, apoE, apoM, LCAT, ABCA1 and SR-BI, are rich in HREs (51,87,92). In vitro and in vivo studies have confirmed the binding of several NRs in these sites in response to various intracellular and extracellular ligands.…”
Section: The Impact Of Nuclear Receptors On Hdl Metabolismmentioning
confidence: 99%